Endothelial Cell Inflammation and Barriers Are Regulated by the Rab26-Mediated Balance between β2-AR and TLR4 in Pulmonary Microvessel Endothelial Cells. (28th April 2019) - Chen, Huaping; Yuan, Ming; Huang, Chunji; Xu, Zhi; Li, Mingchun; Zhang, Chun; Gao, Zhan; Zhang, Mingzhou; Xu, Jiancheng; Qian, Hang; You, Jiegen; He, Binfeng; et al.
Abstract : Rab26 GTPase modulates the trafficking of cell surface receptors, such as G protein-coupled receptors including α 2-adrenergic receptors in some cell types. However, the effect of Rab26 on β 2-adrenergic receptor ( β 2-AR) trafficking or/and Toll-like receptor 4 (TLR4) expression in human pulmonary microvascular endothelial cells (HPMECs) is still unclear. Here, we investigated the role of Rab26 in regulating the expression of β 2-ARs and TLR4 in HPMECs and the effect of these receptors' imbalance on endothelial cell barrier function. The results showed that there was unbalance expression in these receptors, where β 2-AR expression was remarkably reduced, and TLR4 was increased on the cell membrane after lipopolysaccharide (LPS) treatment. Furthermore, we found that Rab26 overexpression not only upregulated β 2-ARs but also downregulated TLR4 expression on the cell membrane. Subsequently, the TLR4-related inflammatory response was greatly attenuated, and the hyperpermeability of HPMECs also was partially relived. Taken together, these data suggest that basal Rab26 maintains the balance between β 2-ARs and TLR4 on the cell surface, and it might be a potential therapeutic target for diseases involving endothelial barrier dysfunction.